2020
DOI: 10.1101/2020.10.01.323147
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Megasphaerain the stool microbiota is negatively associated with diarrheal cryptosporidiosis

Abstract: Background: The protozoan parasites in the Cryptosporidium genus cause both acute diarrheal disease and subclinical (i.e. non-diarrheal) disease. It is unclear if the microbiota can influence the manifestation of diarrhea during a Cryptosporidium infection. Methods: To characterize the role of the gut microbiota in diarrheal cryptosporidiosis, the microbiome composition of both diarrheal and surveillance Cryptosporidium-positive fecal samples was evaluated using 16S rRNA gene sequencing. Additionally, the micr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Communication between the enteric nervous system and the central nervous system, which is also affected by SCFAs, has similarly emerged with a potential link to BP. This ability of Megasphaera to produce SCFAs or to modulate the host’s immune system may be protective in attenuating disease during infection [48]. Although the abundance of Megasphaera was increased in our study, the level of SCFAs in patients with HTN was decreased [10, 25].…”
Section: Discussionmentioning
confidence: 68%
“…Communication between the enteric nervous system and the central nervous system, which is also affected by SCFAs, has similarly emerged with a potential link to BP. This ability of Megasphaera to produce SCFAs or to modulate the host’s immune system may be protective in attenuating disease during infection [48]. Although the abundance of Megasphaera was increased in our study, the level of SCFAs in patients with HTN was decreased [10, 25].…”
Section: Discussionmentioning
confidence: 68%
“…Increased abundance of Prevotella has been previously linked to Dietary-Fiber induced improvements in glucose metabolism (20), weight loss responses to speci c diets and obesity management (21). Megasphaera's role the gut microbiota has not been thoroughly researched yet, some studies showed that its lowered abundance correlates with severity of Diarrheal Cryptosporidiosis (22) while others focus on its role in female reproductive health (23). Literature search for the role of Pseudorhodobacter in gut microbiota and in the gut brain axis returned no studies.…”
Section: Discussionmentioning
confidence: 99%
“…According to this result, an increase in the abundance of Megasphaera has been described in colon content and faeces of pigs fed with iron-deficient diet [57]. Interestingly, this genus was reported as a potential biomarker for immune-mediate mechanism of protection from diarrhea [58] and positive correlated with luminal IgA concentration in pigs [49].…”
Section: Discussionmentioning
confidence: 99%